GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 19 Oct 2019, 17:51

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If (x - 6) (2x + 1) = 0, and x > 0, then x =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58445
If (x - 6) (2x + 1) = 0, and x > 0, then x =  [#permalink]

Show Tags

New post 19 Feb 2018, 22:55
00:00
A
B
C
D
E

Difficulty:

  15% (low)

Question Stats:

91% (00:50) correct 9% (01:31) wrong based on 56 sessions

HideShow timer Statistics

Senior Manager
Senior Manager
User avatar
P
Joined: 07 Jul 2012
Posts: 367
Location: India
Concentration: Finance, Accounting
GPA: 3.5
Re: If (x - 6) (2x + 1) = 0, and x > 0, then x =  [#permalink]

Show Tags

New post 19 Feb 2018, 23:05
1
(x-6)=0; x=6

OR

(2x+1)=0; x=\(\frac{-1}{2}\)

Since X>0

So x=6

Answer: A.
_________________
Kindly hit kudos if my post helps!
Senior Manager
Senior Manager
User avatar
G
Joined: 31 May 2017
Posts: 334
GMAT ToolKit User Reviews Badge
If (x - 6) (2x + 1) = 0, and x > 0, then x =  [#permalink]

Show Tags

New post 20 Feb 2018, 22:12
To get= (x - 6)(2x + 1) = 0 one of the equation should be equal to zero

(x-6) = 0 , to get this solution, there is only one logical value for x among the answer choice , X =6.

The other value (2x + 1) cannot be zero since X > 0 and all positive values of x will only result in positive value.

Ans: 6 (option A)
_________________
GMAT Club Bot
If (x - 6) (2x + 1) = 0, and x > 0, then x =   [#permalink] 20 Feb 2018, 22:12
Display posts from previous: Sort by

If (x - 6) (2x + 1) = 0, and x > 0, then x =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne